Construction of Modern Islamic Inheritance Law based on Ijtihad of the Judges at the Religious Court of Pontianak, West Kalimantan - Hasan, Muhammad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This article is motivated by the asymmetry connection between the growing discourses and applications of Islamic inheritance law in the Pontianak society and religious court decisions. In contrast, the decision of the religious court (Peradilan Agama, the Indonesian term, abbreviated for PA) must be implemented. This is an empirical legal study employing a legal sociology methodology. In-depth interviews, analysis of PA decision documents, and Focus Group Discussions (FGD) with Pontianak PA judges were used to collect data. This study concludes that the construction of inheritance law by Pontianak PA judges employing the legal discovery method is more influential in terms of adhering to jurisprudence and evaluating inheritance provisions contained in fiqh texts. The judge's legal reasoning is based on socio-cultural reasoning, which examines the relationship between rights and family responsibilities in society. Among the inheritance provisions of the judge's ijtihad construction is 1) the restriction on substitute successors does not apply only to second-degree descendants, but to all descendants. 2) Daughters become the asabah in heritance even if they are not accompanied by males or sons. 3) Children of unrecorded marriages have the right to maintenance and obligatory wills from their fathers. The novel finding of this study is that, according to the sociology of law, local traditions in the application of inheritance law occupy a strategic position and contribute significantly to the manner in which judges construct law in court decisions, particularly Islamic inheritance.